Dielectric properties of four room temperature ferroelectric and antiferroelectric multi-component liquid crystalline mixtures. Issue 2 (26th January 2019) - Debnath, Asim; Mandal, Pradip Kumar
ABSTRACT: Dielectric properties of four recently formulated room temperature multi-component liquid crystalline mixtures with paraelectric (SmA*), ferroelectric (SmC*) and antiferroelectric (SmC*A ) phases have been studied as a function of temperature and frequency. Under planer anchoring condition, dielectric spectroscopy revealed all the characteristic modes: low frequency PL and high frequency PH mode in SmC*A phase, Goldstone mode (GM) in SmC* phase and soft mode (SM) in SmA* phase. Dielectric behaviour has also been studied under the application of DC bias electric field. With bias electric field, we have been able to study the soft mode dielectric behaviour in the SmC* phase. An unknown high frequency mode (X-mode) with and without bias is also observed in SmC* phase. Dielectric results are explained in the light of generalised Landau theory. The mixtures show very high soft mode electroclinic coefficient in the SmA* phase in addition to fast switching in SmC*A and SmC* phases [30]. GRAPHICAL ABSTRACT: